Tratamiento de aguas residuales mediante sistema de zanjas de filtro y filtros subsuperficiales de arena para pequeñas redes de abastecimiento - Mite Bedoya, Alexander Wilfrido (2017)
The present work identifies the problem of contamination and diseases caused by the direct discharge of sewage to adjacent channels and the use of blind wells in Miraflores Site. The research was carried out between May and August of 2017, with the objective of elaborating an alternative of wastewater treatment design by means of filter trenches and subsurface sand filters for small supply networks at the Miraflores site Parish of Bellavista. A pre-feasibility study was carried out investigating all the current alternatives for wastewater treatment and choosing the alternative that meets the socioeconomic, topographical and soil conditions of the site. For the soil studies the first to perform were the infiltration tests in situ, which consisted of performing gauges at different depths, 30 m apart, the first one was done in the first layer discarding the organic soil, for that the calicata had Dimensions of 0.80 by 0.80 m inside this one were elaborated cylinder of 0.30 m of diameter by 0.30 m of depth, to these cylinders were placed 5 cm of gravel and they were filled in 66% with water during a period of 24 hours, This saturation made it possible to simulate the operating conditions of the treatment plant. After 24 hours, the water was taken every half hour for a period of 3 hours. The procedure was repeated for the remaining gauges. Different depths where the different strata are located. The second was the extraction of soil samples for analysis in the laboratory, for which moisture content tests and Atterberg boundaries were performed, followed by the results obtained to classify the soil using the unified soil classification system (SUCS) . Laboratory tests classified the first stratum in OL - ML, the second stratum was classified as CH, and the third stratum was classified as OH - MH. The results obtained from the in situ infiltration tests determined the presence of completely impermeable strata, since they completely prevent the passage of water through them, which is why it was proposed the implementation of subsurface sand filters with drainage systems. These filters consist of 75% sand, 25% gravel and at the top the placement of a geotextile that allows the evaporation of the waste water and retains fines that can enter from the filling material to the filter, the design is Complemented with a drainage system in order to direct the effluent to the nearest receiving body. In the proposed design, the dimensions of the subsurface filters were increased in order to efficiently distribute and collect the wastewater, this design allowed to comply with the availability of existing land in the study area, since the entire plant occupies 2434.00 m2, a saving of 50% of land compared to the design of filter trenches, which generates savings in the implementation of different structures and in the overall cost of the treatment plant.